ACTIVE TECHNOLOGIES OF PREPARING A CHILD FOR SCHOOL (Pedagogy of Higher and Secondary Education, 2010)
In article the authors analyzes the outstanding teachers position as for the necessity of the childrens preparation to school and the technology of this preparation.
Keywords: preparation for school; school readiness; intellectual commitment; personal commitment; strong-willed readiness training activities